Understanding the medical diagnosis of child maltreatment a guide for nonmedical professionals - Brittain, Charmaine (New York : Oxford University Press, 2005)
"Provides a step-by-step guide to frequently asked questions concerning the medical aspects of child abuse and neglect. Designed for the nonmedical professional, this guide covers burns, fractures, poisoning, sexual abuse, neglect, substance abuse, and working with medical providers. Includes charts, illustrations, checklists, and resources"--Provided by publisher.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Child abuse -- Diagnosis; Battered child syndrome -- Diagnosis; Electronic books